Review of the report of improper medical care (pre-investigation check) – what the anesthesiologist and emergency physician should know - K. G. Shapovalov; S. A. Sumin; R. A. Yaroslavkin (Вестник анестезиологии и реаниматологии)
The objective: to raise the awareness of medical professionals about one of the stages of investigation – pre-investigation check.Results: the article presents the information on the legal aspects of the review of a report on medical crime (pre-investigation check). It outlines potential legal consequences for a physician at this stage of the legal proceedings. Lawyers' advice on the principles of conduct for a medical professional during pre-investigation checks is discussed. Physicians, who are the subject for the review of a report on medical crime are advised to take active participation in the proceedings, to clarify the circumstances of the case and potential legal consequences. At the same time, they are recommended to use affirmative defense based on existing regulations and get experienced lawyers involved.